Effect of Prevalence and Severity of Molar-Incisor Hypomineralization on Oral Health-Related Quality of Life: A Systematic Review and Meta-Analysis - Abdelrahman Awwad; Rakan Hamad; Ulrich Schiffner; Christian H. Splieth; Julian Schmoeckel (Acta Stomatologica Croatica, 2023)
Objectives: The aim of this systematic review and meta-analysis is to assess the association between the MIH presence as well as the severity and OHRQoL in children. Material and methods: Relevant studies were identified in PubMed, Embase, Cochrane and Google Scholar. Studies involving MIH and OHRQoL in children were included. A methodological quality assessment of included studies was performed using the Newcastle-Ottawa Scale (NOS) and its adapted version for cross-sectional studies. Random effects models were used to estimate summary effect measures for the association between MIH presence (presence vs. absence) as well as severity (moderate/severe MIH vs. no MIH) and OHRQoL using generic inverse variance meta-analyses. Tests for heterogeneity, publication bias and sensitivity of results were also performed. Results: Out of 1696 identified publications 11 studies reporting on 5,017 children were included in the meta-analysis assessing the impact of MIH presence. There was no statistically significant association between the presence of MIH and lower OHRQoL in affected children (OR = 1.72, 95% CI = 0.99–2.98). Concerning MIH severity and its impact on OHRQoL, a sum of 6 studies were included in the meta-analysis involving a total of 2,595 children. There was a significant association between moderate/severe MIH and lower OHRQoL in affected children (OR = 3.43, 95% CI = 1.69–6.98). Conclusion: Moderate/Severe MIH has a significant and clinically relevant negative impact on OHRQoL, and it should therefore be addressed adequately. Future research should also consider the impact of a uniform MIH diagnosis and precise severity criteria.